PENGARUH MEDIA SOSIAL DAN PERSEPSI HARGA TERHADAP MINAT BELI KONSUMEN DENGAN CITRA MEREK SEBAGAI MEDIASI PADA UMKM KAMPUNG LAUK PALANGKA RAYA - Dendy, Dendy; Meitiana, Meitiana; Peridawaty, Peridawaty; Budiman Bancin, John (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the influence of social media and price perception on consumer purchase intention with brand image as a mediating variable at UMKM Kampung Lauk Palangka Raya. The research method employed a quantitative approach using Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis on 97 respondents who are consumers of UMKM Kampung Lauk. The results show that social media has no significant effect on brand image (t-statistic 0.420, p-value 0.675), but has a significant negative effect on consumer purchase intention (t-statistic 2.447, p-value 0.014). Price perception has a very strong positive effect on brand image (t-statistic 11.313, p-value 0.000) with a path coefficient of 0.801, but does not directly affect consumer purchase intention (t-statistic 0.105, p-value 0.917). Brand image significantly and positively influences consumer purchase intention (t-statistic 3.339, p-value 0.001) with a path coefficient of 0.489. Mediation testing indicates that brand image does not mediate the influence of social media on purchase intention (Direct-only nonmediation), but fully mediates the influence of price perception on consumer purchase intention (Indirect-only mediation) with a coefficient of 0.392. This study concludes that brand image is a highly dominant key factor in increasing consumer purchase intention, and positive price perception must first establish a good brand image before it can drive purchase intention. UMKM Kampung Lauk needs to optimize its social media strategy and maintain price consistency with product quality to strengthen brand image and increase consumer purchase intention.